Statement following the United Nations’ Chief Executives Board Meeting on Ebola, Washington, D.C., November 21, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group discusses efforts of the leaders of the United Nations system toward the Ebola epidemic, and their work toward a unified approach on the ground in West Africa. The goal is to get to zero cases. He talks about the need for community-based care facilities with well-trained health workers and strong triage, diagnostic, treatment and referral capabilities in the affected countries. He speaks about the need to accelerate and adapt the response to changing conditions on the ground and also prepare for the recovery. He assured continued support as development partners to the Ebola-affected countries.